2018
DOI: 10.3389/fmicb.2018.01763
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Insights Into Composition, Metabolic Potentials, and Interactions Among Archaeal, Bacterial, and Viral Assemblages in Meromictic Lake Shunet in Siberia

Abstract: Microorganisms are critical to maintaining stratified biogeochemical characteristics in meromictic lakes; however, their community composition and potential roles in nutrient cycling are not thoroughly described. Both metagenomics and metaviromics were used to determine the composition and capacity of archaea, bacteria, and viruses along the water column in the landlocked meromictic Lake Shunet in Siberia. Deep sequencing of 265 Gb and high-quality assembly revealed a near-complete genome corresponding to Nonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 100 publications
0
23
0
Order By: Relevance
“…A study from Lake Biwa (38) reported that Ͼ65% of viral genomes were unique to a particular depth. Similarly to Lake A data, a study of Lake Shunet, a sub-Arctic meromictic lake in Siberia (39), showed that very few viral taxa were present throughout the water column. However, in this study, the highest relative viral diversity was observed in the surface stratum.…”
Section: Discussionmentioning
confidence: 81%
“…A study from Lake Biwa (38) reported that Ͼ65% of viral genomes were unique to a particular depth. Similarly to Lake A data, a study of Lake Shunet, a sub-Arctic meromictic lake in Siberia (39), showed that very few viral taxa were present throughout the water column. However, in this study, the highest relative viral diversity was observed in the surface stratum.…”
Section: Discussionmentioning
confidence: 81%
“…M30B3, abbreviated as M30B3. The M30B3 is the predominant bacterium in Lake Shunet at 3.0 m and plays a pivotal role in providing organic carbon in the lake ecosystem [12].…”
Section: Resultsmentioning
confidence: 99%
“…Using comparative genomics, unique and intriguing metabolic features are identified in these complete MAGs, including two predominant novel species: Thiocapsa sp, and Cyanobium sp. [12]. The findings show that it is advantageous to apply this method in studies of microbial ecology and microbial genomics by revising and improving the shortcomings of SRs-based metagenomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations